Using Searcher Simulations to Redesign a Polyrepresentative Implicit Feedback Interface - White, Ryen W. (Information Processing and Management (IP&M), 2006)
Information seeking is traditionally conducted in environments where search results are represented at the user interface by a minimal amount of meta-information such as titles and query-based summaries. The goal of this form of presentation is to give searchers sufficient context to help them make informed interaction decisions without overloading them cognitively. The principle of polyrepresentation (Ingwersen, 1996) suggests that Information Retrieval (IR) systems should provide and use different cognitive structures during acts of communication to reduce the uncertainty associated with interactive IR. In previous work we have created contentrich search interfaces that implement an aspect of polyrepresentative theory, and are capable of displaying multiple representations of the retrieved documents simultaneously at the results interface. Searcher interaction with content-rich interfaces was used as Implicit Relevance Feedback (IRF) to construct modified queries. These interfaces have been shown to be successful in experimentation with human subjects but we do not know whether the information was presented in a way that makes good use of the display space, or positioned most useful components in easily accessible locations, for use in IRF. In this article we use simulations of searcher interaction behaviour as design tools to determine the most rational interface design for when IRF is employed. This research forms part of the iterative design of interfaces to proactively support searchers.